Mapping of Damar Mata Kucing (Shorea javanica) Plus Trees in Repong Damar Penengahan Village, Karya Penggawa Sub District, West Pesisir Regency, Lampung Province - Muhammad Ridwan; Afif Bintoro; Rahmat Safe’i (Journal of Sylva Indonesiana, 2021)
The distribution of seed and plus tree sources of damar mata kucing (Shorea javanica) in Repong Damar village is important to provide good quality of seeds. Currently, the existence of seed source of damar mata kucing is still unknown. Based on these conditions, it is necessary to mapping the seeds source or damar mata kucing plus trees. This study aims to analyze the plus tree map distribution using geographic information systems. This research was conducted using a survey method to determine the coordinates based on the growth location characteristics. Data analysis was performed using geographic information systems. The results showed that there were 24 plus trees (17.5%) of the total population studied and distributed in 3 location, namely east, north and west part. The plus tree distribution is mostly in the eastern part of 58.3%, the northern part is 20.8%, and the western part is 20.8%. The growth location conditions in the eastern part has a slope of 5 - 15%, with an altitude of 41 - 121 m.asl. In the western part it has a slope of 5 - 7%, with an altitude of 40 - 73 masl and the northern part has a slope of 5 - 15%, with an altitude of 35 - 174 masl.